Medical librarianship at the college of librarianship, Wales 1988/1989 - Chan, S.N. (Perpustakaan Universiti Malaya, 1989)
The author describes the contents and events of a one-year study leave while pursuing the Medical Library course at the College of Librarianship, Wales, during the-1981 89 academic session. Her impressions of two major dental libraries in London are also recorded.